Boronic acid-containing aminopyridine- and aminopyrimidinecarboxamide CXCR1/2 antagonists: Optimization of aqueous solubility and oral bioavailability. Issue 18 (15th September 2015) - Schuler, Aaron D.; Engles, Courtney A.; Maeda, Dean Y.; Quinn, Mark T.; Kirpotina, Liliya N.; Wicomb, Winston N.; Mason, S. Nicholas; Auten, Richard L.; Zebala, John A.
Graphical abstract: Abstract: The chemokine receptors CXCR1 and CXCR2 are important pharmaceutical targets due to their key roles in inflammatory diseases and cancer progression. We have previously identified 2-[5-(4-fluoro-phenylcarbamoyl)-pyridin-2-ylsulfanylmethyl]-phenylboronic acid (SX-517) and 6-(2-boronic acid-5-trifluoromethoxy-benzylsulfanyl)- N -(4-fluoro-phenyl)-nicotinamide (SX-576) as potent non-competitive boronic acid-containing CXCR1/2 antagonists. Herein we report the synthesis and evaluation of aminopyridine and aminopyrimidine analogs of SX-517 and SX-576, identifying (2-{(benzyl)[(5-boronic acid-2-pyridyl)methyl]amino}-5-pyrimidinyl)(4-fluorophenylamino)formaldehyde as a potent chemokine antagonist with improved aqueous solubility and oral bioavailability.